ANTIHYPERTENSIVE AND TOXICITY STUDIES OF AQUEOUS METHANOLIC EXTRACT OF MENTHA LONGIFOLIA L. - Alamgeer; M. S. Akhtar; Q. Jabeen; S. Bashir; M. N. H. Malik; H. U. Khan; M. S. U. Rahman; U. Salma; U. Mazhar; A. Qa. Khan; M. Islam (Journal of Animal and Plant Sciences, 2013)
The present study was conducted to investigate the effect of the aqueous methanolic extract of Mentha longifolia, L on blood pressure of both normotensive and hypertensive (egg- feed and glucose- induced) rats. The effect of the extract on systolic, diastolic, mean blood pressures and heart rate were evaluated by using non-invasive blood pressure measurement apparatus (NIBP). The extract at doses of 500 and 1000 mg/kg (p.o) exhibited a significant decrease in blood pressure and heart rate of normotensive rats. While at the dose of 100mg/kg (p.o) it did not produce any significant effect. The 1000mg/kg of the extract produced a highly significant effect was selected for antihypertensive effect in egg feed and glucose treated hypertensive rats. A significant antihypertensive and negative chronotropic effects were observed at 1000 mg/kg (p.o) in both hypertensive models. Acute and sub-chronic studies were carried out and median lethal dose (LD50) of the extract was found to be 3.75 g/kg in mice. The extract did not produce any mortality or signs of toxicity in mice and rats. In addition, a non-significant decrease in ALT, AST, and ALP but significant decrease in total cholesterol, triglycerides, LDL and increase in HDL levels were observed in the serum of the extract treated animals. It is conceivable, therefore, that the aqueous: methanolic extract of Mentha longifolia, L possesses safer active principles which exert both hypotensive and antihypertensive effects in normal and hypertensive animal models respectively.
Keywords: Mentha longifolia; L.; aqueous: methanolic extract; non-invasive; antihypertensive